If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2m + -5 + -2(m + -2) = 3m + -1(4m + -6) + -5m + 1 Reorder the terms: -2m + -5 + -2(-2 + m) = 3m + -1(4m + -6) + -5m + 1 -2m + -5 + (-2 * -2 + m * -2) = 3m + -1(4m + -6) + -5m + 1 -2m + -5 + (4 + -2m) = 3m + -1(4m + -6) + -5m + 1 Reorder the terms: -5 + 4 + -2m + -2m = 3m + -1(4m + -6) + -5m + 1 Combine like terms: -5 + 4 = -1 -1 + -2m + -2m = 3m + -1(4m + -6) + -5m + 1 Combine like terms: -2m + -2m = -4m -1 + -4m = 3m + -1(4m + -6) + -5m + 1 Reorder the terms: -1 + -4m = 3m + -1(-6 + 4m) + -5m + 1 -1 + -4m = 3m + (-6 * -1 + 4m * -1) + -5m + 1 -1 + -4m = 3m + (6 + -4m) + -5m + 1 Reorder the terms: -1 + -4m = 6 + 1 + 3m + -4m + -5m Combine like terms: 6 + 1 = 7 -1 + -4m = 7 + 3m + -4m + -5m Combine like terms: 3m + -4m = -1m -1 + -4m = 7 + -1m + -5m Combine like terms: -1m + -5m = -6m -1 + -4m = 7 + -6m Solving -1 + -4m = 7 + -6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6m' to each side of the equation. -1 + -4m + 6m = 7 + -6m + 6m Combine like terms: -4m + 6m = 2m -1 + 2m = 7 + -6m + 6m Combine like terms: -6m + 6m = 0 -1 + 2m = 7 + 0 -1 + 2m = 7 Add '1' to each side of the equation. -1 + 1 + 2m = 7 + 1 Combine like terms: -1 + 1 = 0 0 + 2m = 7 + 1 2m = 7 + 1 Combine like terms: 7 + 1 = 8 2m = 8 Divide each side by '2'. m = 4 Simplifying m = 4
| 2n+2(n+7)+1=39 | | 2y+2(y+1)=-6 | | 85+55x=y | | y=120+16(x) | | 2-6=a+a+4 | | -4p-3(4-3p)=2(p-4)-22 | | 3r+5(r-1)=27 | | 5(x+3)=8(x+6) | | 14x+12=4x^2 | | 4(r+6)=-49 | | -8x+48=-2(x-2)(x-2)+32 | | X+-1=0 | | -3(r+7)=-40 | | X+-2=0 | | 10(v+2)-2v=2(4v+3)-9 | | 2.87x+25.83=51.66 | | 5r^2=48+r | | -4(r+3)=-61 | | -10x+4=-7x+13 | | 9y-7=28 | | 6(x-2)=(x-4)-28 | | .3x+5=x+3 | | 18x-30= | | .3x+.5=1-0.05x | | f(X)=x^2+6x+1 | | (2x+10)+(6x-4)= | | -7-3y=14 | | 10+25b= | | 8w-6.4=-6.4+5w | | x^2-26x+138=0 | | 1.98g-14=0.89 | | 3(6c-2)=4(10c-7) |